The Role of Outdoor Media and "Solo Berseri" Magazine in Enhancing the Effectiveness of Surakarta Municipal Program Promotion - Aulia Suminar Ayu; Novita Haryono; Sri Hastjarjo; Andrine Prima Afneta Arzil; Widyantoro (Aptisi Transactions On Technopreneurship (ATT), 2023)
This study aimed to provide input and evaluation for the Surakarta City Communication, Information, Statistics, and Encryption Service in measuring the effectiveness of their information dissemination work programs. Conducted as a descriptive quantitative research with a sample size of N = 30, the study assessed the media consumption patterns of Surakarta City residents and the affordability of the promotional media used by the Solo City Government. The findings of this study revealed that the magazine "Solo Berseri" possesses sufficient attractiveness and informational value, meeting the gratification needs of its readers. However, the limited accessibility of this magazine hampers its effectiveness as a promotional medium. These results emphasize the importance of ensuring accessibility and distribution channels for promotional materials. Addressing the limited accessibility of "Solo Berseri" would enhance its impact as a promotional medium for the Solo City Government. Additionally, the findings suggest that the strategic placement of billboards can effectively reach the target audience and disseminate important information. Based on these findings, recommendations can be made for the Surakarta City Communication, Information, Statistics, and Encryption Service to improve their information dissemination strategies. Implementing measures to increase the accessibility of "Solo Berseri" and exploring additional affordable promotional media channels could enhance the effectiveness of their communication efforts. By incorporating these suggestions, the Surakarta City Government can enhance their communication efforts and ensure that important information reaches and resonates with the residents effectively